Brazilian Food Guide attacked. Now, overwhelming support for the Guide in Brazil and worldwide - Carlos Augusto Monteiro; Patrícia Constante Jaime (World Nutrition, 2020)
The present commentary summarizes the attacks to the Dietary Guidelines for the Brazilian Population from ultra-processed food manufacturers and the Brazilian Ministry of Agriculture, Livestock and Supply (MAPA). After MAPA issued a technical note calling on the Ministry of Health urgently to review the Guide by cutting out its recommendation to avoid consumption of ultra-processed food products, without citing scientific evidence, a wide group of scholars confirmed that the note had no valid foundation.